Patricio's crown. Living with HIV in Puebla (Mexico): embodying the disease, embodying homosexuality (Anclajes, 2024)
The corpus is made up of a compilation of stories about the experience of being homosexual and living with the human immunodeficiency virus (HIV) made up of a series of in-depth interviews, situated ethnographic records and informal conversations carried out during the year 2022 with a man homosexual who lives with HIV in Puebla, Mexico — and who is named Patricio—. Some of the semiotic-material intersections through which his experiences are configured are analyzed. In addition, certain imaginary figures are highlighted, the affects in which his modes of interaction are framed, some journeys of his daily life and his possibilities of containment in the face of discriminatory practices and stigmatizing scenarios. In three moments, some of the ways in which, between the ways of embodying an illness and the ways in which homosexuality is embodied, are exposed, these dimensions seem to be sustained by the cultural mark —always historical, always political— of shame and pride.
Keywords: HIV/AIDS; Disease; Homosexuality; Homophobia; Emotions